Kinetics and mechanism of CO2 gasification of coal catalyzed by Na2CO3, FeCO3 and Na2CO3–FeCO3. Issue 3 (June 2020) - Xu, Bang; Cao, Qingxi; Kuang, Dongyang; Gasem, Khaled A.M.; Adidharma, Hertanto; Ding, Dong; Fan, Maohong
Abstract: The purpose is to develop a mild catalytic CO2 -gasification technology that can promote CO2 utilization and reduce cost in air separation systems with improving system efficiency and obtaining desirable gaseous products. In this study, the influence of Na, Fe and their composite catalysts on the structure and gasification reactivity of chars derived from pyrolysis of Powder River Basin (PRB) coal was investigated. The results showed that a strong positive synergistic effect between Na and Fe catalyst in the gasification process was observed, the catalytic activity of the added catalysts was in order of: 4% Na > 3% Na–1%Fe > 2% Na-2% Fe > 1% Na-3% Fe > 1% Na-2% Fe > 4% Fe > raw coal. The catalysts inhibited the growth of the aromatic ring structure and enriched the generation of O-containing functional groups. Compared to Fe, the Na-based catalyst could easily diffuse into inner pores of coal char, forming C–O–Na structure and thus increasing the gasification reactivity of chars. In addition, due to the formation of inert material between SiO2 and Na, the catalytic activity of Na catalysts was significantly decrease at the late stage of char conversion. Comparatively, the Fe-based catalysts showed better stability life. Moreover, it was found that the activation energy for CO2 -gasification of PRB coal can be decreased by 50% due to the addition of Na catalyst. Graphical abstract: Image 1 Highlights: Influence of Na–Fe catalysts on char-CO2 reaction was examined. Synergistic effect between Na and Fe catalyst was clearly observed. Physico-chemical structure evolution of chars was systematically characterized. Activation energy of gasification can be decreased by 50% with use of Na2 CO3 .